What issues facilitate and constrain the use of value capture mechanisms by the state in Uganda : case study of Kampala-Entebbe Express Highway - Mwesigye, Ian Kananura (Department of Construction Economics and Management, 2017)
The purpose of the research was to examine the issues that constrain and facilitate the use of value capture mechanisms by the state in Uganda. Considering that limited research had been undertaken on value capture in Uganda, an exploratory case study approach was used to identify and investigate the issues associated with the use of value capture in Uganda. The identified case study was the Kampala-Entebbe Express Highway. The methodology involved collection of data using the survey method and desktop review of relevant documentation. The survey method was conducted using face to face interviews with carefully selected respondents that were knowledgeable in the subject matter of the research. Both qualitative and quantitative data were collected. The qualitative data was analysed using thematic analysis with the assistance of Nvivo, a qualitative data analysis tool while descriptive statistics was used to analyse the quantitative data. The findings of the research showed that value is created from the provision of public transport infrastructure. However, there are issues that may constrain the capture of this created value. These included insufficient valuation of land parcels and registration of land ownership, the existing land tenure system, gaps in the policy and legal framework and insufficient institutional capacity.